2011
DOI: 10.1242/dev.063511
|View full text |Cite
|
Sign up to set email alerts
|

The control of developmental phase transitions in plants

Abstract: SummaryPlant development progresses through distinct phases: vegetative growth, followed by a reproductive phase and eventually seed set and senescence. The transitions between these phases are controlled by distinct genetic circuits that integrate endogenous and environmental cues. In recent years, however, it has become evident that the genetic networks that underlie these phase transitions share some common factors. Here, we review recent advances in the field of plant phase transitions, highlighting the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
508
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(532 citation statements)
references
References 112 publications
(168 reference statements)
19
508
2
3
Order By: Relevance
“…4) (refs 29,31). SPL9, À 10, À 2, À 3, À 11, À 13 and À 15 have been shown to function similarly and redundantly with each other in regulation of the juvenile-to-adult phase transition and flowering time [29][30][31][32][33][34][35][36] . SPLs also feedback-regulate miR156 precursor transcription 29 .…”
Section: Resultsmentioning
confidence: 99%
“…4) (refs 29,31). SPL9, À 10, À 2, À 3, À 11, À 13 and À 15 have been shown to function similarly and redundantly with each other in regulation of the juvenile-to-adult phase transition and flowering time [29][30][31][32][33][34][35][36] . SPLs also feedback-regulate miR156 precursor transcription 29 .…”
Section: Resultsmentioning
confidence: 99%
“…7). miR156 and miR172 have been identified as key components of the mechanisms that underlie the transition from juvenile to adult phase (Huijser and Schmid, 2011); however, although the roles of these miRNAs have been studied extensively, the mechanisms involved in their regulation are still largely unknown, especially those related to the age-dependent decline of miR156. We found that plants impaired in AtBMI1 function showed increased levels of MIR156A/C at the time the levels of miR156 should decline, which indicates that AtBMI1 proteins are required for miR156 repression.…”
Section: Discussionmentioning
confidence: 99%
“…During the juvenile-to-adult phase transition, plants acquire competence to flower as well as undergo changes in multiple traits, such as leaf size and shape, internode length, and trichome distribution (Huijser and Schmid, 2011;Poethig, 2013). Although PcG proteins may have a role in regulating this developmental transition, the severity of the phenotype in some PcG mutants or the lack of phenotype in others has concealed their possible implication.…”
mentioning
confidence: 99%
“…In animals, there are some reports of transcription factors directly associating with pri-miRNA genes and resulting in the expression or repression of the associated genes (Hino et al, 2008;Xiong et al, 2009;Zhou et al, 2010;Zhang et al, 2012b). In Arabidopsis and other angiosperms, miR156 and miR172 are regulators of phase transitions, with miR156 delaying phase transitions while miR172 promotes the progression through the life cycle (for review, see Huijser and Schmid, 2011). Several direct regulators of miR172-encoding genes have been identified, including the MADS factor SHORT VEGETATIVE PHASE, which is involved in the repression of pri-miR172a (Cho et al, 2012), and SPL9, which leads to an accumulation of miR172 (Wu et al, 2009).…”
Section: Fus3 and Genes Regulated In Response To Supraoptimal Temperamentioning
confidence: 99%